(untitled) (Fiep Bulletin - online, 2013)
The conception of the body constantly changes through its history. The way like it is noticed, defined and sense comes through the time evidencing the characteristics of a society, a culture. The history of a person’s life is registered in his/her body: defining posture, it sorts things out of moving, if it expresses, marking his/her skin. To "be shemale" for PELUCIO (2005), it is a process, that he/she never closes up. To build a body and to take care him/it is one of the shemale´s largest concerns. They are always looking for "perfection", the one that means "pass for woman". it is in the coexistence in the prostitution territories that shemales incorporate the values and forms of the feminine, they take knowledge, the tricks and techniques of the daily of the prostitution, they conform tastes and preferences (especially the sexual ones) and a lot of times win or they adopt a feminine name. The general objective of the study is to get the relative indicators the conception of the body of a group of shemales from Ipatinga´s metropolitan area,and the specific objectives are to Identifying the perception and the function from this body; To describe the aesthetics concept, types of relative cares to the body; To identify if they suffer prejudices, which and what impact has in the behaviors; types of changes that they would like to accomplish in the body and actions carried out in the sense of intervening in the body; if the style of "manners vivendi", activity if the sexual activity is related to the leisure, to the work and if both.